2018
DOI: 10.3389/fgene.2018.00318
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Characterization of Selection Signatures and Runs of Homozygosity in Ugandan Goat Breeds

Abstract: Both natural and artificial selection are among the main driving forces shaping genetic variation across the genome of livestock species. Selection typically leaves signatures in the genome, which are often characterized by high genetic differentiation across breeds and/or a strong reduction in genetic diversity in regions associated with traits under intense selection pressure. In this study, we evaluated selection signatures and genomic inbreeding coefficients, FROH, based on runs of homozygosity (ROH), in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
87
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(119 citation statements)
references
References 87 publications
10
87
2
Order By: Relevance
“…In this study, differences in terms of total number and length of ROH were short (>5Mb) were more abundant (57.61%). [48] reported results that showed lower than the F ROH > 2Mb for Kenya, Uganda, and Mozambique goat breeds when Goat 50K BeadChip was used. On the other hand, the Eastern Cape population showed very low amounts of ROH.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In this study, differences in terms of total number and length of ROH were short (>5Mb) were more abundant (57.61%). [48] reported results that showed lower than the F ROH > 2Mb for Kenya, Uganda, and Mozambique goat breeds when Goat 50K BeadChip was used. On the other hand, the Eastern Cape population showed very low amounts of ROH.…”
Section: Discussionmentioning
confidence: 93%
“…The Illumina goat SNP50K BeadChip includes 53 347 SNPs [59] that have found utility in South African population genetic studies in Angora [27], commercial, indigenous and village goat populations [37] as well as investigate genetic adaptation to environmental pressures [36]. The use of the tool has been described in other African countries [48,65] and in specialised breeds [32]. While much work on South African commercial, indigenous and village goat populations has focused on genetic studies and investigation on genetic adaptation, less work has focused on conservation status and historical relatedness of communal indigenous goat populations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous knock-out results have shown that Vav3deficient mice were protected from bone loss induced by systemic bone resorption stimuli such as parathyroid hormone or RANKL (Faccio et al, 2005). Furthermore, VAV3 is associated with hypothyroidism in humans, food conversion ratio in a male Duroc pig population, high body weight and growth rate in Boer goats, as well as sperm concentration in Holstein-Friesian bulls (Hering et al, 2014;Kwak et al, 2014;Wang et al, 2015;Onzima et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For both POP A and B 284 it was possible to identify short and long segments in most of the animals analyzed, whereas 285 in the POP C a small number of animals (n = 7) presented ROH8-16 Mb and none ROH>16 Mb. 286 In recent years, some studies have investigated different genomic methods to estimate 287 inbreeding coefficients in cattle [12,25,26,45,47,48], pigs [27,28,49,50], goats [51][52][53] and 288 rainbow trout [32]. However, this is the first study aimed at characterizing the ROH patterns 289 and comparing different genomic-and pedigree-based methods to estimate inbreeding 290 coefficients in farmed coho salmon populations.…”
Section: Genomics-and Pedigree-based Inbreeding 278mentioning
confidence: 99%